The Strategic Role of AI in Business Process Transformation and ESG Commitment - Nunes, Tiago; Pinto Borges, Ana; Vieira, Elvira; Vieira, Bruno Miguel (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This paper explores the impact of Artificial Intelligence (AI) on business process optimization, emphasizing its role in fostering sustainable management aligned with ESG (Environmental, Social, and Governance) principles. The study adopts a mixed-methods approach, combining quantitative survey data (n = 152) with qualitative insights from semi-structured interviews with professionals from diverse industries. The results reveal that AI implementation enhances operational efficiency, supports informed decision-making, and contributes to productivity gains. Key benefits include cost reduction, improved customer experience, and reallocation of human tasks to more strategic activities. Despite initial resistance from employees, proper training and change management proved crucial in ensuring successful adoption. The study also highlights challenges such as high implementation costs and ethical concerns. Findings suggest that AI can support long-term sustainable practices by enabling real-time data analysis, process automation, and predictive capabilities. Limitations include the geographical scope constrained to Portugal and the relatively small interview sample. This research provides valuable implications for managers aiming to integrate AI into existing systems to enhance competitiveness while supporting sustainability goals. It adds to the growing body of literature on the intersection of AI, ESG, and sustainable business strategy.